Metropolis 2008. Final report 2002 - 2008. Commission 4. Urban Mobility Management. - (:unkn) unknown (My University, 2009)
Die CD enthält die Dokumentationen der Metropolis Tagungen zu "Urban Mobility Management" der Jahre 2003 - 2008 unter den Titeln: Basic facts on urban mobility / Megapolises of the future / Safeguarding mobility - transforming transportations / Mobility and social cohesion / Financing urban mobility / Urban commercial transport.
Keywords: Verkehr; Mobilität; Stadtverkehr; Verkehrsplanung; Metropole; Agglomeration; Megastadt